Comparison of cognitive functioning of elders with late-life depression and patients with and without a history of depressive episodes: a cross-sectional study. Issue 6 (3rd July 2022) - Rajtar-Zembaty, Anna; Rajtar-Zembaty, Jakub; Olszewska, Katarzyna; Epa, Roksana; Chrobak, Adrian Andrzej; Starowicz-Filip, Anna; Bętkowska-Korpała, Barbara
ABSTRACT: Nowadays there are numerous studies on the occurrence of cognitive dysfunction in late-life depression (LLD). The role of executive dysfunctions in the psychopathology of depression is particularly emphasized and needs further examination. The aim was to assess cognitive functions and their relation to depressive symptoms in elders with LLD, previously depressed, and patients without the history of depressive episodes. The study consisted of 824 older adults who underwent a neuropsychological evaluation (97 currently depressed, 114 previously depressed and 613 patients without the history of depressive episodes). LLD patients performed poorer in ACE-III and AVLT and poorer in TMT-B than those previously depressed and never depressed. The LLD group also performed significantly poorer than the previously depressed on Digit Span Forward. Results of a multiple regression analysis indicated that performance on measures of executive functioning was associated with depression severity in LLD (β =.227, P =.024). The results of this study suggest that executive functions are the most impaired in the elderly with LLD. Furthermore, there is a relationship between executive dysfunction and the severity of depression in LLD. Executive dysfunction appears to be the core neurocognitive deficit in LLD.